PENGARUH CASHBACK, HARGA, DAN FREE ONGKIR TERHADAP IMPLUSIVE BUYING PADA MARKETPLACE TIKTOK SHOP ( Studi Kasus Pada Masyarakat Kota Surakarta ) - Sri Isfantin Puji Lestari; Santosa Tri Prabawa; Novarika Rahmadani (ITB AAS Indonesia Surakarta, 2025)
The purpose of this study is to ascertain how price, free shipping, and cashback affect TikTok Shop on impulsive buying behavior of consumers in Surakarta City. The sample used in this study consisted of 100 respondents who had made at least one purchase through the TikTok Shop app. Primary data from surveys was used in this investigation. The dependent variable in this study is impulsive buying, while the independent factors are cashback, price, and free shipping. The sampling technique used instrument testing, With the aid of SPSS version 26, multiple linear regression analysis, hypothesis testing (f-test & t-test), and R2 coefficient of determination test were conducted. The study's findings indicate that the factors of price, free shipping, and cashback have a favorable and substantial impact on Impulsive Buying among TikTok Shop marketplace users in Surakarta City.